TRACKING MOVING TARGET LOCATION OF MOBILE SENSOR NAVIGATION USING ANT COLONY OPTIMIZATION IN WIRELESS SENSOR NETWORK - Malu B. Reddi, Prof. Dhanashree Kulkarni (International Journal of Research Science and Management, 2015)
Now a days Tracking mobile target is an big problem in wireless sensor network. This work is about the difficulties involved to track the target which emits the signal using the mobile sensor based on reception of signal. As the mobile target plan is unknown, time of arrival (TOA) measurements from the mobile sensor network is used by the mobile sensor controller. Mobile sensor controller collect TOA is obtained from both the mobile target and mobile sensor to direct mobile sensor to follow the target and also to estimate location. To estimate the location we used min max approach. System also proposes Ant colony optimization (ACO) to estimate location efficiently and for managing sensor mobility aiming at improving the tracking of a single target. This enlightens the approximation of the position of the nodes to guess the location of the nodes. Once the entity is managed, mobile sensor nodes concentrate in that entity and the location of the mobile sensor and target jointly to improve the tracking accuracy